The Effect of Intensifications Through Rephrasing on Argument Persuasiveness - Schumann, Jennifer; Oswald, Steve (Informal Logic, 2026)
This paper addresses the role of various forms of intensification on the persuasiveness of rephrased statements in argumentative contexts. Study 1 compares rephrasing through adverbial or verbal intensification to repetition, a similar intensifying strategy, regarding the perceived deservingness (correlated to persuasiveness) of stated outcomes. Results show that adverbial intensifiers create the strongest effect, followed by intensified verbs and repetition. Study 2 examines the effectiveness of rephrasing with intensified verbs compared to rephrasing with intensified objects and repetition. Results indicate that intensifications of the verb yield stronger effects on deservingness/persuasiveness, than intensifications of the object and repetition. Overall, rephrasing through intensification seems to strengthen a justification’s persuasiveness.